THE GENUS TRIGONOSPORA (THELYPTERIDACEAE) IN MALESIA - Holttum, RE (Research Center for Biology, 1974)
The distribution of the genus is discussed, and the Malesian species distinguished and described. Two new combinations are effected, Trigono-spora calcarata (Bl.) Holtt. and T. koorderSiiH (Chr.) Holtt.; the latter is here recognized for the first time as closely related to T. calcarata,.